Karin Michaëlis - en europæisk humanist (Vol. 338):Et portræt i lyset af hendes utopiske roman Den grønne Ø - Birgit Susanne Nielsen (Studier fra Sprog- og Oldtidsforskning, 2006)
The writer Karin Michaëlis was one of the best known Danish writers outside of Denmark in the first half of the 20th century, especially in Germany and Austria. Her novels primarily convey the lives of women at the ages of puberty and menopause and were published in very large print runs, just as her stories about the girl Bibi were among the most read children's books in Europe. Today, hardly anyone remembers her. Taking Michaëlis' early utopian novel as her point of departure, Birgit S. Nielsen sketches an image of the time and a portrait of the colourful artist and unconventional cultural figure, who spent much of her life and a lot of money on helping people in distress. Birgit S. Nielsen, MA, is a senior lecturer in the Department of German and Dutch at the University of Copenhagen.